Multidimensional Aspect of Child Poverty in India. Issue 3 (December 2016) - Radhakrishna, R.; Ravi, C.
This article analyzes incidence of childhood poverty in India and the states in the post-reform period by considering monetary poverty, malnutrition and educational deprivation. It focuses on malnutrition and analyzes the determinants of malnutrition by considering child, mother and household-specific characteristics. It ranks states on their levels of child well-being and also on the progress made in improving the well-being of their children. It also examines whether growth is adequate to eliminate child poverty.